Antimony(V) as Acceptors - Yadav, Ram Nath Prasad (Academic Voices: A Multidisciplinary Journal, 2016)
Lewis acidity of antimony(V) pentahalides and their organo substituted derivatives is well known. SbX5 acts as a strong acceptor towards halide ion as compared to antimony trihalide due to presence of two more electronegative halogen atoms in antimony pentahalide makes it better acceptor. Hexacoordinated organoantimony(V) complexes including chelating ligands are also known and hexacoordination and heptacoordination environment have been suggested for such compounds. The substitution of hydrocarbon groups bound to antimony by trifluoromethyl or pentafluorophenyl groups enhances the Lewis acidity of antimony facilitating the formation of neutral adducts. Such properties have mainly been investigated with organoantimoy(V) halides. As expected successive replacement of an organic group by halogen atom increases acceptor strength of antimony(V) compounds. Academic Voices Vol.5 2015: 34-39